Evaluating the differences in healthy lifestyle behaviors between Chinese urban and rural residency after the termination of social distancing: analysis based on propensity score matching - Yudong Miao; Dongfang Zhu; Zhanlei Shen; Yi Li; Wanliang Zhang; Junwen Bai; Ruizhe Ren; Jingbao Zhang; Dan Guo; Clifford Silver Tarimo; Wenyong Dong; Rongmei Liu; et al. (BMC Public Health)
Abstract Background During the COVID-19 pandemic, the social distancing has significantly affected the healthy lifestyle behaviors of residents. China ended social distancing on January 8, 2023, and the healthy lifestyle behaviors of residents after this time are unclear. The goal of this study was to evaluate the differences in healthy lifestyle behaviors between Chinese urban and rural residency after the termination of social distancing. Methods From February 1, 2023, to February 8, 2023, a cross-sectional survey which include participants (≥ 18 years old) was carried out in four regions of mainland China (Changzhou in the eastern region, Zhengzhou in the central region, Xining in the western region, and Mudanjiang in the northeastern region). A healthy lifestyle behaviors scale containing 11 items was designed to calculate the healthy lifestyle behaviors scores among urban and rural residents. The healthy lifestyle behaviors scores ranged from 11 to 51. Multivariate linear regression was used to analyze the influencing factors of healthy lifestyle behaviors scores among urban and rural residents. Propensity Score Matching was used to assess the net differences in healthy lifestyle behaviors scores between urban and rural residents. Results A total of 5780 residents (53.04% females) were included in the study, including 3302(57.13%) urban residents. The average healthy lifestyle behavior score was 38.33(95%CI: 38.18 to 38.49). Healthy lifestyle behaviors score among males was lower than that among females in both urban (β = -1.98, 95%CI: -3.05 to -2.10) and rural residents (β = -2.57, 95%CI: -2.37 to -1.60). Higher education was associated with higher healthy lifestyle behaviors scores in both urban and rural residents. PSM analysis indicated that urban residents still had higher healthy lifestyle behaviors scores (38.72, 95% CI: 38.46 to 38.99) than rural residents (37.85, 95%CI: 37.57 to 38.13), with a net difference of 0.87 points. Conclusions After the termination of social distancing, the overall healthy lifestyle behaviors of Chinese residents were found to be at a medium level. Urban residents have a better healthy lifestyle behavior compared to their rural counterparts. It is essential to prioritize efforts towards enhancing the healthy lifestyle behaviors of rural residents.